2017
DOI: 10.1590/1516-4446-2017-3904
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met polymorphism and memory performance in older adults: the Met carrier effect is more complex than previously thought: Authors’ reply

Abstract: Rev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In terms of genetic factors, to date, the effect of BDNF Val66Met polymorphism on cognition decline remains controversial. The Val allele may be neuroprotective and related to higher cognition, and Met is related to impaired cognitive function ( Azeredo et al, 2017 ; Barha et al, 2019 ). A recent meta-analysis indicated that performance on memory-based tasks was better in Val/Val carriers ( Toh et al, 2018 ), which is partly consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of genetic factors, to date, the effect of BDNF Val66Met polymorphism on cognition decline remains controversial. The Val allele may be neuroprotective and related to higher cognition, and Met is related to impaired cognitive function ( Azeredo et al, 2017 ; Barha et al, 2019 ). A recent meta-analysis indicated that performance on memory-based tasks was better in Val/Val carriers ( Toh et al, 2018 ), which is partly consistent with our results.…”
Section: Discussionmentioning
confidence: 99%